2013
DOI: 10.1149/2.040403jes
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Layered to Spinel Conversion of a Li-Rich Layered Metal Oxide Cathode Material for Li-Ion Batteries

Abstract: We have prepared the Li-rich layered NMC composite cathode material of the composition 0.3Li 2 MnO 3 0.7LiMn 0.33 Ni 0.33 Co 0.33 O 2 , (NMC) with 5 wt% Na doping. The latter material with composition of 0.3Li 2 MnO 3 .0.7Li 0.97 Na 0.03 Mn 0.33 Ni 0.33 Co 0.33 O 2 , synthesized as 200-300 nm size particles, was compared to its counterpart without Na. The discharge rate capability of the Li-rich NMC was greatly improved at both room temperature and 50 • C with the Na doping. The Na doped material exhibited sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
152
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 51 publications
11
152
0
1
Order By: Relevance
“…[8][9][10]16,25,52 The transformation from layered to spinel is expected to be accelerated by cycling at elevated temperature. [53][54][55] Interestingly enough the high frequency mode around 630 to 650 cm…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10]16,25,52 The transformation from layered to spinel is expected to be accelerated by cycling at elevated temperature. [53][54][55] Interestingly enough the high frequency mode around 630 to 650 cm…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, higher Ni concentrations result in highly unstable Ni 3+ and Ni 4+ ions remaining in the layered structure, and their reaction with the electrolyte speeds up 2 Journal of Nanomaterials degradation of the materials and batteries [10,11]. In order to solve these problems, the small amounts of dopants at the cationic sites have been considered; for example, it has been reported that the addition of small amounts of Cl, Mg, F, and Na improves the capacity and cycle performance [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…19,22,23 However, to obtain such a capacity, these materials must be cycled over a wide potential range of 2.5-4.6 V (vs. Li + /Li), which may be challenging for the current carbonate-based electrolytes. Major issues such as large irreversible capacity (IRC), 19,33,34 voltage fade upon cycling 22,[35][36][37][38][39][40] and poor rate capability 22,41,42 have hindered the application of these materials. * Electrochemical Society Student Member.…”
mentioning
confidence: 99%